2023
DOI: 10.1002/ldr.4607
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of keystone fungal taxa after flue gas desulphurization gypsum application drives reclamation of the saline‐sodic soil

Abstract: Soil salinization is a major threat to sustainable agriculture in the western part of Songnen Plain, Northeast China. Flue gas desulphurization gypsum (FGDG) is commonly used for reclaiming of saline soils due to its high efficiency and cost-effectiveness. However, the responses of soil and root-associated fungi after FGDG amendment and the keystone fungal taxa in determining soil reclamation effect remain elusive. In this study, a long-term field experiment was conducted to explore the effect of different lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
2
0
0
Order By: Relevance
“…The utilization of modified materials has proven effective in improving soil environmental conditions, thus directly affecting microbial diversity and altering the structure of soil microbial communities. Our findings revealed significant variations in soil fungal diversity under different simulated modified materials; in contrast, the same was not observed in the bacterial diversity, consistent with previous findings ( Li et al, 2023 ; Zhang et al, 2023 ). In this study, we observed a significant increase in fungal diversity in response to the application of farm manure.…”
Section: Discussionsupporting
confidence: 91%
“…The utilization of modified materials has proven effective in improving soil environmental conditions, thus directly affecting microbial diversity and altering the structure of soil microbial communities. Our findings revealed significant variations in soil fungal diversity under different simulated modified materials; in contrast, the same was not observed in the bacterial diversity, consistent with previous findings ( Li et al, 2023 ; Zhang et al, 2023 ). In this study, we observed a significant increase in fungal diversity in response to the application of farm manure.…”
Section: Discussionsupporting
confidence: 91%
“…Also, Mortielleromycota and Glomeromycota increased in the treated vines, in accordance with previous works [52,53]. In particular, Glomeromycota was identified as the keystone taxa in predicting the soil salinity soil fertility, and plant growth trait [54].…”
Section: Discussionsupporting
confidence: 91%